Is the Effect of the Exchange Rate on Stock Prices Symmetric or Asymmetric? Evidence from Sudan - Mohamed, Omer Ahmed Sayed; Elmahgop, Faiza Omer Mohammed (International Journal of Economics and Financial Issues, 2020)
This study investigates asymmetry in the effect of the exchange rate on the Sudanese stock market prices. We applied the Nonlinear ARDL model by Shin et al. (2014) to monthly data for the period from September 2003 to September 2019, using inflation, money supply, and Murabaha profit margin as control variables. No study found that test the nonlinearity effect of the exchange rate on stock prices in Sudan. This study proposed to fill this gap by examining the impact of the exchange rate of Sudanese Pound nonlinearity on the stock prices in the Khartoum Stock Exchange. The results show that the exchange rate has asymmetric effects on stock prices in both the short run and long run. The policy implication of this paper is that modeling the exchange rate and stock prices symmetrically may affect negatively the effectiveness of economic planning. Thus, NARDL emerges as a more suitable model than the ARDL model for investigating such a relationship. Keywords: Exchange Rate, Stock Prices, Nonlinear Autoregressive Distributed Lag, Autoregressive Distributed Lag, Asymmetry, Symmetry JEL Classifications: E31, E44, G2 DOI: https://doi.org/10.32479/ijefi.9268